Ependymal Vps35 Promotes Ependymal Cell Differentiation and Survival, Suppresses Microglial Activation, and Prevents Neonatal Hydrocephalus - Wu, Kong-yan (J Neurosci, 2020)
Hydrocephalus is a pathologic condition associated with various brain diseases, including Alzheimer's disease (AD). Dysfunctional ependymal cells (EpCs) are believed to contribute to the development of hydrocephalus. It is thus of interest to investigate EpCs' development and function. Here, we report that vacuolar protein sorting-associated protein 35 (VPS35) is critical for EpC differentiation, ciliogenesis, and survival, and thus preventing neonatal hydrocephalus. VPS35 is abundantly expressed in EpCs. Mice with conditional knock-out (cKO) of Vps35 in embryonic (Vps35(GFAP-Cre) and Vps35(Emx1-Cre)) or postnatal (Vps35(Foxj1-CreER)) EpC progenitors exhibit enlarged lateral ventricles (LVs) and hydrocephalus-like pathology. Further studies reveal marked reductions in EpCs and their cilia in both Vps35(GFAP-Cre) and Vps35(Foxj1-CreER) mutant mice. The reduced EpCs appear to be due to impairments in EpC differentiation and survival. Additionally, both Vps35(GFAP-Cre) and Vps35(Foxj1-CreER) neonatal pups exhibit increased cell proliferation and death largely in a region close to LV-EpCs. Many microglia close to the mutant LV-EpC region become activated. Depletion of the microglia by PLX3397, an antagonist of colony-stimulating factor 1 receptor (CSF1R), restores LV-EpCs and diminishes the pathology of neonatal hydrocephalus in Vps35(Foxj1-CreER) mice. Taken together, these observations suggest unrecognized functions of Vps35 in EpC differentiation, ciliogenesis, and survival in neonatal LV, and reveal pathologic roles of locally activated microglia in EpC homeostasis and hydrocephalus development. SIGNIFICANCE STATEMENT This study reports critical functions of vacuolar protein sorting-associated protein 35 (VPS35) not only in promoting ependymal cell (EpC) differentiation, ciliogenesis, and survival, but also in preventing local microglial activation. The dysfunctional EpCs and activated microglia are likely to induce hydrocephalus.